The Contribution of Corporate Governance to Improving the Reputation of Organizations Comparative Research in Telecommunication Companies - Farah Q. Mohammed,; Sadoon Al-Rebiaw, (International Journal of Psychosocial Rehabilitation, 2020)
This research sought to identify the extent to which corporate governance contributes to improving the reputation of the organization by using the method of comparison between the communications companies in the private sector represented by the Scope Sky Company and the public (government) company represented by the General Company for Communications and Informatics. In particular. The research problem lies in the lack of awareness of public sector administrations of the concept of corporate governance and the challenges they face in competing with private sector goods and services. The importance of the research is that it contributes to assisting the management of organizations in applying corporate governance by applying the principles of fairness and transparency and fighting financial and administrative corruption. Research to clarify how to build a good reputation of the organization. The aim of this research is to know the reality of applying corporate governance in the public and private sectors.The research found that corporate governance contributes and improves the reputation of organizations.